Pengaruh Media Sosial Terhadap Identitas Sosial Remaja Pada Era Digital di SMA Negeri 2 Kota Kupang - Ayu Zeruya Mira Higa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2025)
The study aims to investigate the impact of social media on teenagers' social identities in the digital era at SMAN 2 Kupang. This study employed quantitative methods, and the data were analyzed using SPSS. The data were then collected through questionnaires, observations, and documentation. Two variables were found as a result of this study: (1) the total percentage of influence of social media on students is 88.61%, and (2) the impact of social media on student identity is 87.39%. As a result, it is reasonable to assume that social media has a significant impact on teenagers' social identities in the digital era at SMAN 2 Kupang. In terms of the validity and reliability analysis test findings on the questionnaire, the indicators have an r-table value of 0.36 and a computed r-value of 0.677, indicating that all are valid. However, the reliability test with a rating of 0.858 suggests that it is exceptionally high or highly reliable. In the simple linear regression test, the significant value (sig) of 0.000 is less than <0.05 probability, therefore Ha is accepted. It is concluded that the use of social media influences the social identity of teens at SMAN 2 Kupang.